(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the prevalence of overweight and obesity and to identify associated lifestyle factors among fourth-year students at Hanoi Medical University in 2024. Methods: A cross-sectional study was conducted on a sample of 387 fourth-year students during the 2023-2024 academic year. Data were collected using self-administered questionnaires, including the International Physical Activity Questionnaire (IPAQ) and a modified Food Frequency Questionnaire (FFQ), covering aspects such as dietary habits, physical activity levels, and sleep duration. Statistical analysis was performed with Stata 15.0 software to calculate Odds Ratios (OR) and 95% Confidence Intervals (CI) for associations between lifestyle factors and overweight/obesity. Results: The prevalence of overweight and obesity among the participants was 11%, with 10% overweight and 1% obese. Key factors associated with an increased risk of overweight/obesity included living in rental housing or dormitories (OR = 1.9; 95% CI: 1.01-3.59), low dairy product consumption (OR = 1.72; 95% CI: 1.45-2.0), and low vegetable intake (OR = 3.3; 95% CI: 1.4-3.6). Additionally, students who slept less than 7 hours or more than 10 hours per day had a significantly higher risk of overweight/obesity compared to those who slept 7-8 hours (OR = 0.6; 95% CI: 0.58-0.69; p = 0.001). Conclusion: The prevalence of overweight and obesity among fourth-year students at Hanoi Medical University is 11%, with 10% being overweight and 1% being obese. There is a statistically significant association between students’ overweight/obesity status and factors such as gender, living arrangements, consumption of dairy products, meat and vegetables, and sleep duration.